Effect of plasma oxidation treatment on production of a SiOx/SiOxCyHz Bilayer to protect carbon steel against corrosion - Ribeiro, Rafael P. [UNESP]; Rangel, Rita De Cássia C. [UNESP]; Fernandes, Felipe O. [UNESP]; Cruz, Nilson C. [UNESP]; Rangel, Elidiane C. [UNESP] (FapUNIFESP (SciELO), 2021)
Because of its excellent properties, carbon steel is a material widely used in several sectors. However, it is easily corroded when exposed to the environment. Seeking to remedy this problem, the possibility of coating carbon steel with SiOx/SiOxCyHzfilms generated by deposition and oxidation in low-pressure plasmas was investigated. Specifically, the effects of excitation power of the oxidation plasma on layer thickness, chemical structure, elemental composition, and barrier properties of the obtained coatings were investigated. The coating of the steel with the SiOxCyHzfilm, generated by plasma in an atmosphere of hexamethyldisiloxane (HMDSO), increased the total resistance to the passage of electric current, measured by electrochemical impedance spectroscopy. However, under the condition of moderate power oxidation (50 W), the results point to the creation of a bilayer system with high resistance to electrochemical attack compared to the SiOxCyHzfilm, even though its thickness is less than this.
Keywords: Carbon steel; Corrosion resistance; PECVD; Plasma oxidation; SiOx; SiOxCyHz